1997
DOI: 10.1017/s0305004196001491
|View full text |Cite
|
Sign up to set email alerts
|

Approximate diagonalization in differential systems and an effective algorithm for the computation of the spectral matrix

Abstract: 1. IntroductionIn a recent paper [3], an extended Liouville–Green formulaformula herewas developed for solutions of the second-order differential equationformula hereHere γM(x) ∼Q−¼(x), QM(x) ∼Q−½(x) and εM(x)→0 as x→∞, while M([ges ]2) is an integer and γM and QM can be defined in terms of Q and its derivatives up to order M−1. The general form of (1·1) had been obtained previously by Cassell [5], [6], [7] and Eastham [10], [11, section 2·4]. In particular, the proof of (1·1) in [10] and [11]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 22 publications
(28 reference statements)
0
33
0
Order By: Relevance
“…However, we can use a technique which has been exploited recently [2], §2 (see also [3], §1.7) for improving perturbation terms -that is, replacing them by terms of a smaller order of magnitude. The idea here is to make the approximate identity transformation…”
Section: Improvement Of the Perturbationmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we can use a technique which has been exploited recently [2], §2 (see also [3], §1.7) for improving perturbation terms -that is, replacing them by terms of a smaller order of magnitude. The idea here is to make the approximate identity transformation…”
Section: Improvement Of the Perturbationmentioning
confidence: 99%
“…A system of this type, but with different Λ 1 and R 1 , was considered recently in [2] where is was shown that a sequence of transformations of (9.4) can be defined, by means of which the perturbation R 1 is successively replaced by perturbations of smaller magnitude as x → ∞. Thus in [2] we have (1) term in the asymptotic solution of (9.6) corresponding to (8.11).…”
Section: Asymptotic Seriesmentioning
confidence: 99%
See 3 more Smart Citations